The Adversary System in Canadian Industrial Relations: Blight or Blessing? - Brookbank, C. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
This article attempts to explore the "free System of collective bargaining" in Canada, with a view to gaining insight into the validity and the efficacity of the adversary concept in industrial relations.